"MADARIJ AL-DURUUS AL-‘ARABIYAH” KARYA KH BASORI ALWI : ANALISIS BUKU DAN PEMANFAATANNYA DI PONDOK PESANTREN - Taufiqurrochman, R (Arabi : Journal of Arabic Studies, 2017)
The book "Madarij al-Duruus al-'Arabiyah" compiled by KH Basori Alwi, Head of Pesantren Ilmu al-Qur'an (PIQ) Singosari Malang is one of the most popular textbooks in Indonesia, especially in the seventies to the nineties. Analysis of the book written by the archipelago is very necessary to know the characteristics of textbooks based on local wisdom. The results of this study: from the content aspect, the entire core component of the textbook content has been fulfilled by this book. There is a preface in each volume as a proof of validation of the contents of the book. All validators gave a positive appreciation of the publication of the book "Madarij al-Duruus al-'Arabiyah". The main purpose of this book is the mastery of reading skills (qiraah), talking (muhadatsah), and writing (insya '). Only skill to hear is not visible in the teaching materials. But, hearing skills have been represented in the Qur'an-Tajwid lesson. From the aspect of the foundation of the preparation of teaching materials, the book "Madarij al-Duruus al-'Arabiyah" meets 3 (three) principles of textbook development, namely: (1) socio-cultural; (2) psychological; (3) language-education. From the method aspect, this book uses an eclectic method that combines various strategies. However, the prioritized method is the method of reading (qiraah), the grammar method and the translation method (qawaid wa tarjamah). These three methods include traditional methods because they still rely on the role of teacher (teacher centris). According to the authors of this book, the position of the teacher remains important for beginner students studying Arabic. What's more, there is the phrase: "Methods are more important than teaching materials. However, professional teachers are far more important than teaching methods and materials”.